(untitled) (Fiep Bulletin - online, 2013)
Objectifies to identify the scientific nature of the broadcasted knowledge in the Thematic Work Group Escola (GTT) of the Brazilian Meeting of Sciences of Sport. The study was delimited to the bibliographic research method, analyzing a documental corpus of 111 articles distributed in the annuals of the meetings of 1997, 1999, 2001 and 2003. The data evidenced that the writings Educação Física e Aprendizagem Social, of Bracht (1992), Metodologia do Ensino de Educação Física, of Coletivo de Autores (1992) and the book Transformação Didático-Pedagógica do Esporte, of Kunz (1994) has been constituted as main references to the studies published in the GTT Escola. These data reinforce the idea that in the Physical Education it has been made use and appropriation of the theories by the secondary referential of the self area.